Activation PDGFR-α/AKT Mediated Signaling Pathways in Oral Squamous Cell Carcinoma by Mesenchymal Stem/Stromal Cells Promotes Anti-apoptosis and Decreased Sensitivity to Cisplatin - Wang, Jia; Cui, Ruwen; Clement, Cecila G.; Nawgiri, Ranjana; Powell, Don W.; Pinchuk, Irina V.; Watts, Tammara L. (Frontiers in Oncology, 2020)
Desmoplasia, a hallmark of a head and neck cancer, has both biologic and physiologic effects on cancer progression and chemotherapeutic response. Mesenchymal stem/stromal cells (MSCs), also known as mesenchymal stromal progenitor cells, have been shown to play a role in cancer progression, alter apoptotic responses, and confer resistance to chemotherapy in various carcinomas. The pathophysiology of MSCs with respect to tumorigenesis is widely reported in other cancers and is sparsely reported in oral squamous cell carcinomas (OSCCs). We previously reported paracrine mediated PDGF-AA/PDGFR-α signaling to underlie MSCs chemotaxis in OSCC. Given the poor clinical response to primary chemotherapy, we hypothesized that MSCs may alter cancer cell sensitivity to cisplatin through activation of PDGFR-α mediated signaling pathways. Co-culture of MSCs with human derived OSCC cell lines, JHU-012 and -019, resulted in a significant increase in the production of PDGF-AA and MCP-1 compared to cancer cells grown alone (p<0.005) and was accompanied by an increase in the phosphorylation state of PDGFR-α (p<0.02) and downstream target AKT at S473 (p<0.025) and T308 (p<0.02). JHU-012 and -019 cancer cells grown in co-culture were significantly less apoptotic (p<0.001), expressed significantly higher levels of Bcl-2 (p<0.04) with a concomitant significant decrease in bid expression (p<0.001) compared to cancer cells grown alone. There was a significant increase in the cisplatin dose response curve in cancer cell clones derived from JHU-012 and 019 cancer cells grown in co-culture with MSCs compared to clones derived from cancer cells grown alone (p<0.001). Moreover clones derived from JHU-012 cells grown in co-culture with MSCs were significantly more susceptible to cisplatin following pretreatment with, crenolanib, a PDGFR inhibitor, compared to cancer cells grown alone or in co-culture with MSCs (p<0.0001). These findings suggest that crosstalk between cancer cells and MSCs is mediated, at least in part, by activation of autocrine PDGF-AA/PDGFR-α loop drivingAKT-mediated signaling pathways, resulting in reduced cancer cell sensitivity to cisplatin through alterations in apoptosis.